Relación bioética y jurídica en la manipulación de células madre embrionarias - Sisa Guerra, Marco Patricio (2013)
The scientific panorama always will be led the own ethical-legal dilemma of the technological advance, inasmuch as it faces positions of great ideological load. Without doubt the beginning of the biotechnology has revolutionized concepts and rules that must be analyzed from the deontological scope of the right and the medicine. This it entails the study of the present thesis, starting off of moral and ethical valuations from its conceptualization to the same application in the field of the Bioderecho. Considered the Bioderecho like the new science of the scientific medical task in the application of the novel systems of reproduction through the genetic manipulation and, especially in the obtaining of cellular new line that promise to eliminate many diseases enrolled or in our genetic code, which they come being suppliers from organs and weaves of spare part to measurement that ours are deteriorated, treatments that or are being made with criteria to favor and against, as well as with positive results for patients and expectation for others